Adsorção de metais em solução aquosa pelos processos de batelada e coluna de leito fixo utilizando silsesquioxano funcionalizado com 5-amino-1,3,4-tiadiazol-2-tiol - Bastos, Andréa de Castro [UNESP] (2015)
In this study the oligosilsesquioxane nanoplatform was organofunctionalized with 5-amino- 1,3,4-thiadiazole-2-thiol molecule, resulting in a material so called POSS-ATT. POSS-ATT was characterized through techniques of electron microscopy EDX scan, infrared spectroscopy and Fourier transform. Parameters that affect behavior were analyzed, in the adsorption process, for POSS-ATT, such as pH and time to reach kinetic equilibrium. Results obtained showed that the POSS-ATT is more efficient for pH higher than 5.32 and the contact time needed to achieve equilibrium in adsorption of ions in aqueous solution was 20 minutes for Ni (II), Zn (II) and 30 minutes for Fe(III), Cu(II) and Pb(II). The experimental data obtained for chemical kinetics have been described using pseudo-second order and intraparticle diffusion kinetic models. The POSS-ATT was applied to adsorption of metallic ions Cu (II), Ni (II), Zn (II), Pb (II) and Fe (III) in aqueous solutions via batch processes and fixed bed column. The experimental data for adsorption in batch were better adjusted to the Langmuir model when compared to the models of Freundlich and Temkin. Additionally, the ability of POSS-ATT was evaluated in the adsorption, desorption and regeneration using aqueous feed solution containing mentioned ions through the packed bed column process. Adsorption capacity, by fixed bed column process, of POSS-ATT occurred in the following order Fe> Cu> Ni> Zn> Pb. It was tested the adsorption capacity of Fe (III) by POSS-ATT varying solution concentration, flow feed rate and average particle size. The experimental data obtained for the adsorption process in fixed bed fitted best to the model Yoon-Nelson when compared to models of Clark and Bohart-Admas